MENINGKATKAN KECERDASAN INTERPERSONAL MELALUI METODE BERMAIN PERAN PADA ANAK USIA 5-6 TAHUN DI TK AISYIYAH BAGAN JAWABAGANSIAPIAPI - Yulia Indrasari; Daviq Chairilsyah; Febrialismanto Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The background of this research is underdeveloped interpersonal optimal child among children may not be able: to work together to show the attitude of its leadership, interacting with others, to understand the feelings of others, and empathy.Therefore, researchers make improvements and optimize interpersonal keceradasan perkembangann child according to his age level. The purpose of the implementation of this study was to determine the interpersonal intelligence, to determine the application of the method to play a role in improving interpersonal intelligence, interpersonal intelligence to determine the increase and to find out how high can increase the methods of playing the role of interpersonal intelligence in children aged 5-6 years. This research is a classroom action research conducted in two cycles. In one cycle there are three meetings. Data collection tool used in this study is in the form of observation sheet. The number of samples in this study were 16 children consisted of 10 boys and 6 girls lkaki.Based on the analysis of the assessment process there was an increase of 2 cycles. Improvement occurred, ie from before the action to the first cycle of 35.6%, cycle I to cycle II of 42.9%, and increased from the prior cycle to cycle II of 93.9%. From the results of these studies concluded that through role-play method can improve interpersonal intelligence of children aged 5-6 years in kindergarten Aisyiyah Java Chart Bagansiapiapi Rokan Hilir.Keyword: Children Aged 5-6 Years, Interpersonal Intelligence, Methods Role Playing.